2020
DOI: 10.1117/1.oe.59.1.014113
|View full text |Cite
|
Sign up to set email alerts
|

Lensless fiber-deployed low-coherence interferometer for in-situ measurements in nonideal environments

Abstract: Low-coherence interferometry (LCI) is a well-established optical method used for obtaining geometric measurements, suited for operating in nonideal environments as shown through its use in biomedical science, where it is referred to as optical coherence tomography. However, work on characterizing these technologies' ability to work in-situ within the area of manufacturing is yet to be demonstrated. This research is motivated by the need to develop robust sensors capable of operating in the harsh environment of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It can be seen from Table 1 that a diverse range of applications have already had initial investigation into the use of LCI sensors for monitoring processes. Recent work demonstrating the use of LCI in the domain of a liquid environment has shown that the system is able to provide stable, accurate data during profilometry measurements across various step-heights [12]. An extension of this work demonstrates an embedded LCI sensor for absolute distance measurement of samples operating within a jet of water has also shown significant data stability [13], demonstrating the potential usefulness of the LCI sensor for post-processing verification of parts, utilising a liquid jet for flushing of debris and coolant during measurement.…”
Section: Sensor Applications In Industrymentioning
confidence: 99%
See 4 more Smart Citations
“…It can be seen from Table 1 that a diverse range of applications have already had initial investigation into the use of LCI sensors for monitoring processes. Recent work demonstrating the use of LCI in the domain of a liquid environment has shown that the system is able to provide stable, accurate data during profilometry measurements across various step-heights [12]. An extension of this work demonstrates an embedded LCI sensor for absolute distance measurement of samples operating within a jet of water has also shown significant data stability [13], demonstrating the potential usefulness of the LCI sensor for post-processing verification of parts, utilising a liquid jet for flushing of debris and coolant during measurement.…”
Section: Sensor Applications In Industrymentioning
confidence: 99%
“…As such, further calibration of the system can be undertaken to improve the accuracy of this transfer function. Previous work discovered for one setup that, during measurements in air, this would lead to errors of up to approximately 50 nm and whilst operating in water approximately 100 nm [12]. Hence, depending on the measurement accuracy requirements, further action may be required to compensate for nonlinearities in the system.…”
Section: Extracting Spatial Depth From Spectral Interferogrammentioning
confidence: 99%
See 3 more Smart Citations